Near-Field-Based 5G Sub-6 GHz Array Antenna Diagnosis Using Transfer Learning - Hong Jun Lim (MDPI AG, 2021)
In this paper, we propose a method for near-field-based 5G sub 6-GHz array antenna diagnosis using transfer learning. A classification network was implemented for normal/abnormal operation of the array antenna and the failure of a specific port. Furthermore, a regression network that could predict the amplitude and phase of the excitation signal of the array antenna was employed. Additionally, to accelerate the array antenna diagnosis, several near-field lines were sampled and reflected in the regression network. The proposed method was verified by measuring a fabricated 5G sub-6 GHz band 4<semantics><mspace width="0.166667em"></mspace>×<mspace width="0.166667em"></mspace></semantics>4 array antenna in various scenarios using a divider and coaxial cables. The tests showed that the trained network accurately diagnosed 29 of 30 measurement results.